This should be faster : what's going on? (O'Reilly Media, 2019)
"Software and applications run on a real physical network. Trying to deliver packets across the data center or around the world can pose unique challenges depending on the application and performance requirements because modern networks are a complicated mix of technologies. Understanding the interaction between these components can be challenging when the network and applications are controlled by one administrative entity. It's even more complicated when the underlying resources are leased from an IaaS provider. The complex interplay between the various components can have unwanted effects on applications. Successfully running applications requires you to have some understanding of the various things that may affect performance. André Henry discusses latency and bandwidth, provides a high-level overview of network components and topology, explores software-defined networks (SDNs), shares how various protocols and configuration can affect network performance, and explains buffers and buffer bloat."--Resource description page.